Confronting global capital: Trade union organising for higher wages in Cambodia's garment and footwear industry - CICHON, DAVID (Trinity College Dublin. School of Social Sciences & Philosophy. Discipline of Sociology, 2019)
After almost a decade of declining wages in Cambodia’s garment and footwear industry, worker incomes have steadily improved since 2013. Minimum wages increased from 80USD a month to 170USD a month in just 4 years, an average annual increase of almost 13% above inflation. This is an unusual and unexpected development for the global garment and footwear industry because power imbalances across the supply chain strongly favour capital over labour. The highly competitive environment has allowed brands and retailers to reduce the prices they pay to suppliers which in turn has led to suppressed wage growth for workers. This thesis is interested in how these structural barriers can be overcome and so the core research question addressed here is how are trade unions and their allies organising for higher wages in the Cambodian garment and footwear industry? The research is based on a global ethnographic study design, which enabled an in-depth engagement with global and national trade unions and the wider network of activists and organisations working on improving wages in Cambodia. Data was gathered through in-depth interviews, participant observation during trade union strategy workshops and protests, attendance at the International Labour Conference and engagement with the new ACT initiative on living wages, as well as garment and footwear factory visits. The thesis shows how the Cambodian wage campaign in 2013/2014 was successful because the national trade unions and NGOs together with a network of global activists engaged in a well-coordinated, confrontational, global campaign demanding that brands and retailers, as the most powerful actors in the supply chain, deliver higher wages. The research argues that in the aftermath of the campaign, however, the Cambodian state began to develop a ‘hegemonic labour control regime’. Under this regime trade unions are asked to partake and consent to the reformed, but state controlled minimum wage setting process while simultaneously being restricted in their abilities to strike, demonstrate and organise workers. The research further explored the pathways through which global unions and NGOs supported the wage campaigning and industrial relations work in Cambodia, arguing that decades of global campaigning have led to a transformation in the understanding of responsibility in global supply chains. This has culminated in the ongoing attempt by IndustriALL and a group of brands to develop a supply chain industrial relations framework on wages through the Action Collaboration and Transformation (ACT) process. The ACT process is examined in detail in the Cambodian context. Finally, the thesis examines how the various ‘campaign coalitions’ between national and global unions and national and global NGOs, which were so effective in 2014, deteriorated and transformed as the focus shifted from a confrontational campaign to engagement in industrial relations institutions. The thesis concludes by arguing that effective coordination between national and global trade unions and national and global labour NGOs is important in building leverage across the entire global supply chain and pressuring brands and retailers, factory owners and states into a position where the structural barriers to higher wages in global garment and footwear manufacturing can be overcome. This is crucial if supply chain industrial relations frameworks like ACT are to deliver sustained and substantial improvements for workers.
APPROVED
Keywords: Global Labour Activism, Trade Unions, Wages, Garment and Footwear Sector, Cambodia